HISTORICAL TRAJECTORIES OF HALAL TOURISM POLICIES AND INITIATIVES IN INDONESIA, 1975–2018 - Furqan, Alhilal (ASEAN Journal on Hospitality and Tourism, 2019)
The use of the historical study approach in this paper is to examine how the development and change of both the practice and paradigm of halal tourism in Indonesia. This paper traces the historical trajectories of the development of halal tourism in Indonesia. Qualitative method and document review allow for detailed historical tracing of key halal tourism development plans, initiative sand policies. There are two broad categories namely halal tourism policy and halal destination development as a location-based pioneering development. The analysis highlights how the distinct historical contexts of state involvement shape the present and future characteristics of halal tourism development in Indonesia. The findings suggest that halal tourism is not solely in response to the demand of tourists, but the effort to develop the greatness of Islam to the wider community.